Dystocia due to Dicephalus Dipagus Monster in a Dangi Cow - KHASATIYA, C T; PATEL, D M; DABHI, D M; CHAUDHARI, P P (The Indian Journal of Animal Reproduction, 2023)
A rare case of Dicephalus Dipagus monster causing dystocia and its successful clinical managementin a cow is placed on record.
Keywords: Bovine; Dicephalus Dipagus; Monster fetus